Influence of limited creep feeding on pre- and post-weaning performance of spring born calves - F.K. Brazle; Gerry L. Kuhl; C.E. Binns; K.O. Zoellner; L.R. Corah; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1992)
Spring-born suckling beef calves were offered salt-limited creep feeds containing either high protein, high energy, or energy plus Bovatec® from August 15 to October 15 in a 3- year study. Creep feeding improved (P<.01) daily gain over controls, but no differences were attributable to creep composition. Daily creep feed consumption was somewhat less for the protein fed group, resulting in improved feed conversion compared to the energy-based supplement, with the energy plus Bovatec creep feed intermediate in efficiency. Creep feeding improved 53-day postweaning gains (P<.01). Overall, limited creep feeding boosted both pre- and postweaning performance, with no difference in gain among the three types of creep rations studied.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Limited creep feeding; Protein energy; Suckling calves; Native grass; Bovatec